Evaluasi Kemajuan Proyek Pada Proses Pengendalian Kinerja Waktu Dan Biaya Dengan Metode Nilai Hasil - Ahmad Zaki; Ade Nurdin; Fetty Febriasti Bahar (Universitas Muara Bungo, 2021)
This study has a purpose to analyze the progress of the cost of controlling time performance and with the Result Value method. Project performance is usually an assessment parameter in the success or failure of a project in general. Poor project management can be a bad cause and harm the project. One of the sources that causes poor project performance is usually a mismatch between the budget, implementation period, and the quality of work against the plan. One method of controlling costs and time is known as the Earned Value Method. This concept is a concept of calculating costs in accordance with the work that has been completed (budgeted cost of work performed). Road Preservation Job Packages Sp. Tuan - Bts. Kabupaten Muaro Jambi - Sp. Tiga Batara Gas Plant (Pematang Lumut) is a work package belonging to The Jambi Province Regional I National Road Implementation Unit with the Service Provider PT. Satya Wira Persada. This work package whose source of funds is from the 2021 State Budget has varied daily reports. The author evaluates the performance of the time and schedule on the project by getting the results of time and cost performance on the Road Preservation Work Package of Sp. Tuan - Bts. Kabupaten Muaro Jambi - Sp. Tiga Batara Gas Plant (Pematang Lumut) showed poor performance based on the CV = Rp. -3,037,850.00, CPI = 0.999 1000, SV = Rp. -428.871.785.62 and SPI = 0.935 1000. According to the results of the evaluation using the Value method, the predicted execution time to complete this work package is 380 days, while the time for implementation based on the contract is 360 days so that this project is predicted to experience a 20 day delay in completing the work. The Realization of the Implementation of the Road Preservation Work Package for Sp. Tuan - Bts. Kabupaten Muaro Jambi - Sp. Tiga Batara Gas Plant (Pematang Lumut) is not according to plan, this is based on reports in the twelfth week of progress of 25.680% while the planned progress is 28.554% so that there is a deviation of -2.875%. Road Preservation Work Package project conditions Sp. Tuan - Bts. Kabupaten Muaro Jambi - Sp. Tiga Batara Gas Plant (Pematang Lumut) in the twelfth week reporting period suffered losses when viewed from the cost aspect with the Yield Value method and delays when viewed from the schedule aspect with the Earned Value method